INTERNET OF THINGS: A REVIEW ON THEIR REQUISITE IN THE DIGITAL ERA - S.Vanitha1*, P. Balasubramanie , K. S. Arvind , V.R.Niveditha , Saravanan Elumalai (International Journal of Advanced Science and Technology, 2020)
The Internet of Things is nothing but the amalgamation of connectivity between physical devicesand daily objects. This technology empowers how computers can gather meaningful information inmany ways, interconnect themselves with various enabling technologies like Artificial Intelligence,Big data Analytics, Cloud Computing and many more to track and count everything around us in theirglory. It is also not surprising to note that IoT is considered to be one of the “DisruptiveTechnologies” with potential impacts in various fields like military, agriculture, medical, healthcare,industrial automation and smart living. This paper addresses the need for internet of things, theirconnecting devices, their architectures and popular frameworks and their application. Various visionsof Internet of Things application has been reviewed and discussed in this paper. Furthermore, theshortcomings and research challenges in various applications have been deliberated in detail..